Cutaneous manifestations and dermoscopic findings are important clues to the diagnosis of Talaromyces marneffei in HIV patients with immune reconstitution inflammatory syndrome: A case report and literature review - Kornkanok Chaisuwannarak (2022)
Talaromyces (formerly Penicillium) marneffei is a dimorphic fungus that causes talaromycosis (formerly penicilliosis). The condition is predominantly found in patients with HIV. Important diagnostic clues are a history of living or travelling in endemic areas, and central umbilicated skin lesions. Dermoscopy is particularly useful for providing rapid bedside information, with a round, whitish, amorphous structure being the most common finding. Immune reconstitution inflammatory syndrome (IRIS) may occur. Driven by the initiation of antiretroviral therapy, IRIS is an exaggerated response of T cells to pathogens. Although mycobacterial and cryptococcal opportunistic infections are common with IRIS, a linkage between T. marneffei and IRIS has rarely been reported. Here, we report on a literature review of patients with HIV who developed IRIS associated with talaromycosis. Dermatologists should be aware of the cutaneous and dermoscopic findings of talaromycosis as they provide important clues that enable its early diagnosis and treatment.